Comparative Analysis of Prestressed Girder Beam Method and Box Culvert on Terms of Construction Costs for Kedungpeluk Bridge Design - Lutfi, Muchamad; Tjendani, Hanie Teki; Wulandari, Esti (International Journal Labs, 2025)
The Kedungpeluk Bridge in Sidoarjo Regency collapsed in 2024 due to structural damage, prompting a need for efficient reconstruction methods. This study compared the cost efficiency and implementation time of two bridge designs—pre-stressed concrete beams and Box Culvert. The research used a quantitative approach to collect secondary data from project drawings, cost budget plans (RAB), and S-curves, alongside unstructured interviews with stakeholders. Findings revealed that the Box Culvert design was more cost-effective, requiring Rp. 1,440,254,544.83, compared to Rp. 1,912,436,195.15 for the pre-stressed concrete beams, resulting in a 24.69% cost savings. Moreover, construction with the Box Culvert design was completed in 10 weeks, 28.57% faster than the 14 weeks for the alternative design. These results highlight the Box Culvert as a superior choice for similar infrastructure projects, addressing urgent community needs for reliable transportation. The implications of this research extend to civil engineering practitioners and government agencies, providing a practical reference for future bridge designs that prioritize cost efficiency and timely implementation, thereby promoting enhanced connectivity and economic growth in the region. Further research is recommended to explore environmentally friendly designs and assess long-term performance in various contexts.